Analisis Perilaku Brand Switcing Konsumen ...(Dimas Dan Muchammad Agung) 1 Analisis Perilaku Brand Switcing Konsumen Produk Air Mineral Di Wilayah Kabupaten Banjarnegara - Dimas Bayu Arianto; Muchammad Agung Miftahuddin (Media Ekonomi, 2014)
This study aims to determine the effect of free variable price, inconvenience, core service failure, service encounter failure, response to service, attraction by competitors, ethical problems, and involuntary switching to switching behavior of mineral water brand in the region Banjamegara both partially and simultaneously. And to determine the independent variables that most influence on switching behavior of mineral water in the Banjarnegara. The method used in sampling is purposive sampling, the sampling is based on specific criteria and goals, with criteria respondents who are buying it either weekly or monthly at the distributor or the same store and was in the region Banjamegara. The analytical method used was multiple linear regression test with a significant level (α) 0,1 and the elasticity test. The results of this study concluded that prices, core service failures, service encounter failures and ethical problems are partially no effect on brand switching, with a significant value of 0,838, 0,925, 0,239 and 0,329 more than 0,1. But attraction by competitor and involuntary switching partially significant effect on brand switching, with a significant value of 0,070 and 0,087 is less than 0,1. price, inconvenience, core service failure, service encounter failure, response to service, attraction by competitors, ethical problems, and involuntary switching simultaneously had no effect on brand switching, with a value significantly by 0,141 more than 0,1. involuntary switching variables that most influence on brand switching. This is indicated by the value of E8 > E1, E3, E4, E6 and E7 is 0275 > 0,018, -0,009, 0,153, 0,176 and -0,111. Key words: Price, Inconvenience, Core Service Failure, Service Encounter Failure, Response To Service, Attraction By Competitors, Ethical Problems, Involuntary Switching and Brand Switching.